2014
DOI: 10.4315/0362-028x.jfp-13-540
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Sublethal Injury Kinetics of Staphylococcus aureus in Broth at Low Temperature Storage

Abstract: Low temperatures are widely used to ensure food quality and safety. However, sublethally injured Staphylococcus aureus is an important microbiological safety concern in low temperature food. The objective of this study was to develop predictive inactivation kinetic models for the inactivation and sublethal injury of S. aureus in broth at different temperatures (4 to -18°C) and time points. S. aureus was diluted in tryptic soy broth plus 0.6% (wt/vol) yeast extract (TSBYE) to obtain approximately 10(8) CFU/ml a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In order to determine the inhibition effects of ZnO nanoparticle‐coated film on foodborne pathogens, S. aureus was selected for further study because it is a frequently detected foodborne pathogen in chilled meat samples that has shown high resistance against low temperatures . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to determine the inhibition effects of ZnO nanoparticle‐coated film on foodborne pathogens, S. aureus was selected for further study because it is a frequently detected foodborne pathogen in chilled meat samples that has shown high resistance against low temperatures . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the inactivation mechanism of ZnO nanoparticles on microorganisms under cold conditions, S. aureus was selected as a reference for determining changes in cell morphology, because it is an important and normally detectable foodborne pathogen in meat during cold storage, and has shown a great resistance against low temperature. 15,19 Briefly, four aliquots of late-exponential phase cells were treated with or without 2 g L −1 ZnO nanoparticles at 4 or 37 ∘ C, respectively. After 24 h treatment under aerobic conditions, 1 mL of each culture was centrifuged at 4000 × g for 5 min.…”
Section: Examination Of Cell Morphology By Scanning Electron Microscomentioning
confidence: 99%
See 1 more Smart Citation
“…Freezing is widely used to ensure the safety and quality of food. However, previous research has shown that low temperatures are sublethal to S. aureus ; at low temperatures, the S. aureus cell itself is damaged, but not dead ( Suo et al, 2014 ). The sublethally injured cells are hard to detect because of their sensitivities to selective components, such as high concentrations of sodium chloride, that are widely used in selective enrichment media ( Wu, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the 4°C condition, freezing causes more damage to the cell membrane because of the formation of ice crystals ( Archer, 2004 ). Damage to the cell membrane leads to the leakage of cellular content, the disruption of membrane permeability, and the weakening of the osmoregulation ability of the cell ( Wesche et al, 2009 ; Suo et al, 2014 ). This damage also reduces the fluidity of the cell membrane and reduces the enzyme activity, according to a study on Listeria monocytogenes ( Schmid et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%